2009
DOI: 10.1007/s10551-009-0345-0
|View full text |Cite
|
Sign up to set email alerts
|

Ethics Instruction and the Perceived Acceptability of Cheating

Abstract: academic cheating, business ethics course, GPA, Machiavellianism, passive cheating,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 46 publications
1
31
0
2
Order By: Relevance
“…The most common form of cheating is plagiarism and it can be deliberate or accidental -many students state that they did not know they were copying, when in fact they were-, a condition which offsets the gravity of the crime but does not make it disappear (Bloodgood, Turnley, & Mudrack, 2010;Roberts, 2008). A series of studies reveal a students' wide and persistent tendency to cheat, and the undergraduates' outcomes reporting this inclination reach more than 80% in the United States (McCabe, Treviño, & Butterfield, 2001) and more than 50% in Canada (Jurdi, Hage, & Chow, 2012).…”
Section: Academic Cheatingmentioning
confidence: 99%
“…The most common form of cheating is plagiarism and it can be deliberate or accidental -many students state that they did not know they were copying, when in fact they were-, a condition which offsets the gravity of the crime but does not make it disappear (Bloodgood, Turnley, & Mudrack, 2010;Roberts, 2008). A series of studies reveal a students' wide and persistent tendency to cheat, and the undergraduates' outcomes reporting this inclination reach more than 80% in the United States (McCabe, Treviño, & Butterfield, 2001) and more than 50% in Canada (Jurdi, Hage, & Chow, 2012).…”
Section: Academic Cheatingmentioning
confidence: 99%
“…Educating young people with regard to ethical conduct, even though it might not bring the expected results immediately, makes them more likely to take an ethical decision in the future (Bloodgood et al, 2010). Research results support the idea that teaching people how to behave ethically in various situations improves understanding of ethical issues and leads to ethical behaviour (Gautschi & Jones, 1998) as well as significantly improving ethical attitudes among students (Weber & Glyptis, 2000).…”
Section: Discussionmentioning
confidence: 58%
“…The individual attitude towards a silent and passive approach of witnesses to situations where others cheat and teachers reward plagiarised work was investigated using the Scale of Acceptance of the Passivity of a Witness of Cheating and Plagiarism. It was developed for my research, similarly to the Scale of Acceptance of Cheating and Plagiarism by Bloodgood et al (2010), in accordance with the applicable procedure. The items were: (1) being silent when you see that somebody is copying another classmate's paper during an exam, (2) being silent when you witness using unauthorized notes (a ''cheat sheet'') during an exam, (3) being silent when you know that your teacher has given your classmate a very good mark for plagiarized work.…”
Section: Methodsmentioning
confidence: 99%
“…To properly evaluate students' views on ethical issues, a survey was utilized to form the conclusion that teaching ethics has an impact on students' personal beliefs and behaviors throughout the course of their lifetime 6 . However, Bloodgood et al (2010) suggested that teaching ethics can have an adverse impact on students who obtain a high score on Machiavellianism 1 . Machiavellianism can be defined as the "implementation of cunning activities and cheating in general conduct.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The primary concern of this instruction should enhance the ethicality of the students to make decisions individually 1 . Hence, the improvement of ethics education in the engineering curriculum is necessary.…”
Section: Introductionmentioning
confidence: 99%